"The Fitting Word" - Beran, Ondřej (My University, 2023)
In his post-war writings, Wittgenstein makes several comments on particularly “fitting” (treffende) words. However, the nature of this quality remains unclear and elusive. In this paper, I present some suggestions about what one might learn from Wittgenstein’s comments, though my purpose is not primarily exegetical, but rather simply to reflect upon what makes a word “fitting”. I discuss several options; first that it is the context what makes the word fitting, then that it is an “imponderable” quality it has. Eventually, I opt for the explanation that the fittingness has (at least often) to do with the enthusiastic feeling the word can give rise to. The feeling should not be construed as a mental event of a private kind, though; rather, we can describe in these terms the dynamics of conversational situations that feature “fitting” words.
"Výstižné slovo"
Keywords: language; fitting word; Wittgenstein; jazyk; výstižné slovo; Wittgenstein